Utilización de 2 niveles de harina de sigse (cortaderia nítida) en reemplazo de una fuente de carbohidratos en la alimentación de pollos de engorde en la parroquia Ignacio Flores. - Herrera Condorcana, Jessica Paulina (2023)
The project was carried out with the objective of using two levels 2 and 4 % of sigse flour in replacement of a source of carbohydrates in the feeding of broilers, the research was carried out in the Ignacio Flores parish of the city of Latacunga, province from Cotopaxi. 96 one-day-old bb chickens of the Cobb500 line were used, they were randomly distributed into 3 groups composed of 32 birds each and 4 repetitions per group: T0 (Basic diet - control treatment), T1 (Basic diet + 2% of sigse flour) and T2 (Basic diet + 4% of sigse flour). The bromatological, microbiological and physical characterization of the sigse flour, obtained from the leaves of the plant, was carried out. This research lasted 56 days and weekly data on weight, food consumption, among others, were collected for further analysis. In the results analysis stage, different productive parameters were calculated to assess the response in chickens when consuming sigse meal as a replacement for a carbohydrate source in their diet. The results presented significant statistical differences (P<0.01) and (P<0.05) between the treatments, thus being the best of the results in final weight (3516.33 g) and weight gain (686.34 g) T2 (4% sigse flour). Regarding the benefit / cost index, the best treatment with the highest profitability was T2 (4% sigse flour) of 1.21 USD, for each dollar invested a net benefit of 0.21 USD was obtained, that is to say that this food helps to decrease the rate of costs in relation to the price of corn.